Limiar de dor no assoalho pélvico, função sexual e autoimagem genital de idosas com e sem fibromialgia - Schlemmer, Gessica Bordin Viera (2018)
Sexual function represents an important component of health, quality of life and interpersonal relationships. Patients with fibromyalgia may present with musculoskeletal pain in other bodily regions beyond classic points, such as in the pelvic floor, often impairing sexual function and altering genital self-image. However, despite the great relevance of this knowledge, there are few studies on this subject, and more studies are needed in this area. In view of this, this study sought to compare sexual function, pelvic floor pain and genital self-image of elderly women with and without fibromyalgia. A descriptive and cross-sectional study was conducted with a quantitative approach with patients from the Hospital Universitário de Santa Maria, where data were collected from 28 elderly women according to the eligibility criteria for sexual function (Female Sexual Function Index, evaluated through FSFI ), female Genital Self-Image Scale (FGSIS), and pain threshold on the pelvic floor by algometry. With the results, two articles were elaborated. The first presents a comparison of the perception of genital self-image and sexual function of the elderly with (GFM) and without fibromyalgia (GS). Regarding sexual function, there was difference between the groups (p <0.038), and GFM presented worse sexual function. There was no difference between the genital autoimaging of the two groups. Already in the second article are the results regarding the evaluations on the pressure threshold of pelvic floor pain in elderly women with and without fibromyalgia. GFM presented lower values for pain perception in relation to the GS group (p <0.000 for the left side) and (p <0.001 for the right side). From this study, it is evident the importance of the multidisciplinary health team to care for these elderly women, including with regard to pelvic floor dysfunctions. It is also observed the need for further studies with this theme.